2015
DOI: 10.1038/srep12986
|View full text |Cite
|
Sign up to set email alerts
|

Highly Pathogenic Avian Influenza A(H5N1) Virus Struck Migratory Birds in China in 2015

Abstract: Approximately 100 migratory birds, including whooper swans and pochards, were found dead in the Sanmenxia Reservoir Area of China during January 2015. The causative agent behind this outbreak was identified as H5N1 highly pathogenic avian influenza virus (HPAIV). Genetic and phylogenetic analyses revealed that this Sanmenxia H5N1 virus was a novel reassortant, possessing a Clade 2.3.2.1c HA gene and a H9N2-derived PB2 gene. Sanmenxia Clade 2.3.2.1c-like H5N1 viruses possess the closest genetic identity to A/Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 42 publications
1
53
0
Order By: Relevance
“…Additionally, other countries should also be on the alert for the potential introduction of this virus into their territories, as exemplified by the introduction of Clade 2.3.4.4 H5N1 viruses into North America and Europe during late 2014 (Jhung and Nelson, 2015;Verhagen et al, 2015). A successful example for outbreak control was the H5N1 outbreak amongst whooper swans in Sanmenxia during January 2015, in which high risk regions for virus transmission along the flyways (such as inner Mongolia) were alerted immediately (Bi et al, 2015a), which helped their preparations and in turn played a considerable role in controlling the outbreak. In addition, human infections with Clade 2.3.2.1c viruses constitute an important reminder of the public health risks from migratory birds carrying H5N1.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, other countries should also be on the alert for the potential introduction of this virus into their territories, as exemplified by the introduction of Clade 2.3.4.4 H5N1 viruses into North America and Europe during late 2014 (Jhung and Nelson, 2015;Verhagen et al, 2015). A successful example for outbreak control was the H5N1 outbreak amongst whooper swans in Sanmenxia during January 2015, in which high risk regions for virus transmission along the flyways (such as inner Mongolia) were alerted immediately (Bi et al, 2015a), which helped their preparations and in turn played a considerable role in controlling the outbreak. In addition, human infections with Clade 2.3.2.1c viruses constitute an important reminder of the public health risks from migratory birds carrying H5N1.…”
Section: Discussionmentioning
confidence: 99%
“…All of the sequences were aligned and phylogenetically analyzed. The HA phylogeny revealed that all of the novel sequences belonged to Clade 2.3.2.1c ( Figure 1) and were closely related to sequences isolated from Sanmenxia, China, where HPAI H5N1 viruses caused the deaths of approximately one hundred migratory birds (mostly whooper swans) between late 2014 and early 2015 (Bi et al, 2015a). Notably, the Chinese strains also clustered together with those from Russia, West Asia, Europe and Africa that were isolated during May 2015, winter of 2014 (Naguib et al, 2015), and spring of 2015 (Monne et al, 2015), respectively (Figure 1).…”
Section: Phylogenetic Analysismentioning
confidence: 99%
See 3 more Smart Citations